Masterpieces of Kabuki : eighteen plays on stage - Brandon, James R.; Leiter, Samuel L. (University of Hawai'i Press, 2004)
Masterpieces of Kabuki contains eighteen outstanding dramas taken from the landmark four-volume series Kabuki Plays On Stage. Together they cover the entire spectrum of kabuki drama from 1697 to 1905, the period during which kabuki's dramaturgy flourished prior to the onset of Western dramatic influence. Major playwrights, chronological periods of playwriting, and a variety of play types (history, domestic, and dance dramas) and performance styles are represented. All but one are in the current repertory and regularly staged. The volume includes introductions to each play and a new general introduction highlighting kabuki's historical development and relating the plays to their performance context. As the subtitle implies, the plays are translated as if "on stage." Stage directions indicate major scenic effects, stage action, costuming, makeup, music, and sound effects. In some cases, complex stage actions such as stage fights are given in detail. The plays collected here are all marvelous examples of dramatic writing, intended to be acted on the stage before audiences. They reveal kabuki's eras of brilliance and bravado, villainy and vengeance, darkness and desire, and restoration and reform. All continue to stir audiences to admiration and excitement